Green Start-Ups’ Attitudes towards Nature When Complying with the Corporate Law - Rafael Robina-Ramírez; Antonio Fernández-Portillo; Juan Carlos Díaz-Casero (Complexity)
This paper examines how Spanish green start-ups develop improved attitudes towards nature. Despite the prevalence of theories based on green entrepreneurs, very little research has been conducted on how green attributes influence nature in the framework of the new Spanish Criminal Code in what concerns corporate compliance. One hundred and fifty-two start-ups were interviewed in 2018. Smart PLS Path Modelling has been used to build an interaction model among variables. The results obtained have a significant theoretical and practical implication since they add new findings to the current literature on how start-ups incorporate the recent Criminal Code in their environmental decisions. The model reveals a strong predictive power (R-squared = 77.9%). There are grounds to say that start-ups should implement effective monitoring systems and new organisational standards, in addition to developing surveillance measures to avoid unexpected sanctions.